Influência do custo da produção no fluxo de caixa de obras de edificações - Minari Junior, Carlos Francisco (2009)
In the context of construction companies, in general, planning is understood as the task of generating a plan and not as a management process. In most cases, the control is focused on management contracts, than in production. Also, note that these companies do not specify the manner in which they can develop and implement systems for planning and production control. Therefore, in order to assist in the understanding of production management, as well as the cost data, this paper deals with the reflection of Integrated Planning and Control the Cost of Production with the cash flow of the work from the budget pre-prepared and information regarding the process in this phase. Based on financial projections, or outflow of funds in cash flow are obtained parameters for administration of the work. We studied three construction companies that use different strategies and administrative management tools. This paper proposes the end the generic representation of the flow of information relating to the process studied. Thus, this analysis constitutes a contribution can provide agility, formality and support the decision-making to managers.